Pelatihan Penggunaan Modal Auxiliary dalam Menulis Kalimat Permintaan - Ida Ayu Panuntun; Inayatul Ulya (DIMASEKA, 2023)
Communication in the global era requires doer of the communication mastering English. In line to this condition, English is a necessity in education, including in Pekalongan. Many students of the second grade of SMP N 5 Pekalongan, often face difficulties in using modal auxiliary when constructing request sentences and it will affect the use of politeness strategies. This phenomenon occurs between teachers and students, or even among students. Based on the root of the problem, Team of PkM held a Training on the Use of Modal Auxiliary in Writing Request Sentences. The sample of this PKM activity was 33 students. PkM was held in 6 months, in the academic year of 2022/2023. PkM activity was done in 4 stages, namely socialization, training, mentoring and evaluation. This activity was carried out well. Each stage in the activity supports the plan to achieve the objectives of PkM. The result was measured from the results of the pre-test and post-test as a comparison in formulating the level of success. The results of the questionnaire showed an increase in aspects of understanding the aspect of auxiliary capital with the score (Good), examples of auxiliary capital (Very Good), its use (Very Good) and the social status of conversation actors (Good). Through this activity, students can distinguish and choose the appropriate use of modal auxiliary according to social status or age.